2017
DOI: 10.1002/chem.201700507
|View full text |Cite
|
Sign up to set email alerts
|

B‐Site Cation Ordered Double Perovskites as Efficient and Stable Electrocatalysts for Oxygen Evolution Reaction

Abstract: Simple disordered perovskite oxides have been intensively exploited as promising electrocatalysts for the oxygen evolution reaction (OER) towards their application in water splitting, reversible fuel cells, and rechargeable metal-air batteries. Here, the B-site cation-ordered double perovskites Ba Bi Sc Co O , with two types of cobalt local environments, are demonstrated to be superior electrocatalysts for OER in alkaline solution, demonstrating ultrahigh catalytic activity. In addition, no obvious performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 46 publications
1
44
0
Order By: Relevance
“…This is a good indication of the improved OER kinetics on the perovskite catalyst incorporating silicon because catalysts having a smaller Tafel slope tend to deliver significantly increased currents at only moderate increments of overpotential. A detailed comparison with literature results, as tabulated in Supplementary Table 4, suggests that the Si-incorporated Si-SCO catalyst compares favourably to the state-of-the-art perovskite catalysts such as BSCF, PBC and SNCF, among many others [7][8][9][10][11][12][13]18,19,31,[42][43][44][45][46][47] .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…This is a good indication of the improved OER kinetics on the perovskite catalyst incorporating silicon because catalysts having a smaller Tafel slope tend to deliver significantly increased currents at only moderate increments of overpotential. A detailed comparison with literature results, as tabulated in Supplementary Table 4, suggests that the Si-incorporated Si-SCO catalyst compares favourably to the state-of-the-art perovskite catalysts such as BSCF, PBC and SNCF, among many others [7][8][9][10][11][12][13]18,19,31,[42][43][44][45][46][47] .…”
Section: Resultsmentioning
confidence: 92%
“…Indeed, the best perovskites show performance comparable to (if not higher than) Ir-/Ru-based standards, especially in alkaline media 5,6 . Typical examples include single perovskite Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3−δ (BSCF) and double perovskite PrBaCo 2 O 5+δ (PBC), which have both been shown with exceptional intrinsic activity in alkaline electrolytes, in some cases several orders of magnitude higher than the IrO 2 benchmark [7][8][9][10][11][12][13] .…”
mentioning
confidence: 99%
“…The atom arrangement in the alloy core of the Fe 3+ -CuNi is disordered while the Cu 1− x NNi 3− y core has an definite atom arrangement due to the antiperovskite structure, which can facilitate the adsorption of OH − , thus promoting the OER activity. 43 Besides, the Ni and Cu in the antiperovskite exist in form of Ni 0 , Ni 2+ and Cu 0 , Cu 2+ , respectively, while the Ni 2+ and Cu 2+ in the alloy only exist on surface resulting from the partially surface oxidation. It is acknowledged that higher oxidation state Cu 2+ /Ni 2+ species are more favorable for OER than the Cu 0 /Ni 0 species.…”
Section: Discussionmentioning
confidence: 99%
“…[49] Such double perovskites (general formula A 2 B′B′′O 6 ) allow for ordering of the transition metal cations in the B site which in turn results in improved OER activity. [50] An equivocal analysis of the perovskite oxygen evolution activity is further complicated by variability of the oxygen evolution mechanism observed for different perovskites. It was shown that, in the case of Sr and Ca perovskite based on Fe and Co, the OER mechanism depends on the nature of the B site cation.…”
Section: Acid Mediamentioning
confidence: 99%